Exercise training prevents cardiovascular derangements induced by fructose overload in developing rats - Farah, Daniela (2016)
The risks of chronic diseases associated with the increasing consumption of fructose-laden foods are amplified by the lack of regular physical activity and have become a serious public health issue worldwide. Moreover, childhood eating habits are strongly related to metabolic syndrome in adults. Thus, we aimed to investigate the preventive role of exercise training undertaken concurrently with a high fructose diet on cardiac function, hemodynamics, cardiovascular autonomic modulation and oxidative stress in male rats after weaning. Male Wistar rats were divided into 4 groups (n = 8/group): Sedentary control (SC), Trained control (TC), Sedentary Fructose (SF) and Trained Fructose (TF). Training was performed on a treadmill (8 weeks, 40-60% of maximum exercise test). Evaluations of cardiac function, hemodynamics, cardiovascular autonomic modulation and oxidative stress in plasma and in left ventricle (LV) were performed. Chronic fructose overload induced glucose intolerance and an increase in white adipose tissue (WAT) weight, in myocardial performance index (MPI) (SF:0.42±0.04 vs. SC:0.24±0.05) and in arterial pressure (SF:122±3 vs. SC:113±1 mmHg) associated with increased cardiac and vascular sympathetic modulation. Fructose also induced unfavorable changes in oxidative stress profile (plasmatic protein oxidation- SF:3.30±0.09 vs. SC:1.45±0.08 nmol/mg prot; and LV total antioxidant capacity (TRAP)-SF: 2.5±0.5 vs. SC:12.7±1.7 uM trolox). The TF group showed reduced WAT, glucose intolerance, MPI (0.35±0.04), arterial pressure (118±2mmHg), sympathetic modulation, plasmatic protein oxidation and increased TRAP when compared to SF group. Therefore, our findings indicate that cardiometabolic dysfunctions induced by fructose overload early in life may be prevented by moderate aerobic exercise training.